Exercise in patients with inflammatory bowel diseases: current perspectives - Engels M; Cross RK; Long MD (Clinical and Experimental Gastroenterology, 2017)
Michael Engels,1 Raymond K Cross,1 Millie D Long2 1Department of Medicine, Division of Gastroenterology and Hepatology, University of Maryland School of Medicine, Baltimore, MD, USA, 2Department of Medicine, Division of Gastroenterology and Hepatology, University of North Carolina at Chapel Hill, NC, USA Abstract: Inflammatory bowel diseases (IBDs), including both Crohn’s disease (CD) and ulcerative colitis (UC), are chronic autoimmune diseases. Both CD and UC have relapsing and remitting courses. Although effective medical treatments exist for these chronic conditions, some patients do not respond to these traditional therapies. Patients are often left frustrated with incomplete resolution of symptoms and seek alternative or complementary forms of therapy. Patients often search for modifiable factors that could improve their symptoms or help them to maintain periods of remission. In this review, we examine both the published evidence on the benefits of exercise clinically and the pathophysiological changes associated with exercise. We then describe data on exercise patterns in patients with IBDs, potential barriers to exercise in IBDs, and the role of exercise in the development and course of IBDs. While some data support physical activity as having a protective role in the development of IBDs, the findings have not been robust. Importantly, studies of exercise in patients with mild-to-moderate IBD activity show no danger of disease or symptom exacerbation. Exercise has theoretical benefits on the immune response, and the limited available data suggest that exercise may improve disease activity, quality of life, bone mineral density, and fatigue levels in patients with IBDs. Overall, exercise is safe and probably beneficial in patients with IBDs. Evidence supporting specific exercise recommendations, including aspects such as duration and heart rate targets, is needed in order to better counsel patients with IBDs. Keywords: inflammatory bowel diseases, Crohn’s disease, ulcerative colitis, exercise, physical activity